Multi-unit assignment under dichotomous preferences - Josué Ortega (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
I study the problem of allocating objects among agents without using money. Agents can receive several objects and have dichotomous preferences, meaning that they either consider objects to be acceptable or not. In this set-up, the egalitarian solution is more appealing than the competitive equilibrium with equal incomes because it is Lorenz dominant, unique in utilities, and group strategy- proof. Both solutions are disjoint.
Keywords: C78; D73; 330; dichotomous preferences; multi-unit assignment; Lorenz dominance; competitive equilibrium with equal incomes